Comparative Study of Biogas Production from Sugarcane Bagasse and Cow Dung - Badiyya Hassan Mashi (UMYU Journal of Microbiology Research)
Renewable energy such as the Biogas has recently been receiving attention. This may be connected to numerous advantages including energy security, and sustainability. However, several challenges including amount of gas produce, nature of substrate, high cost of production remains a problem. This research aimed at investigating biogas production from sugarcane bagasse, cow dung and co-digestion of the two substrates. In this research, sugarcane bagasse which is one of the most common wastes cellulosic materials was used as substrate to generate gas and to compare the rate of production with the most common substrate use (cow dung). Sample of sugarcane bagasse and cow dung ware obtain from Katsina metropolis. Samples were initially, processed (dried, and ground to powder) before preparing slurry in a specialize bioreactor that was constructed using a 900g tin. Three different sets of biogas were made including reactor containing co-digestion of bagasse with cow dung, cow dung alone and sugarcane bagasse alone. The gas generated was allowed only one passage via a tube and collected by downward delivery. The result shows that the digester containing co-digestion of sugarcane bagasse and cow dung has the highest cumulative biogas generation of 74.00 cm3, followed by the digester containing cow dung only which produces a total volume of 52.00 cm3, while  the digester containing sugarcane  bagasse only has  a  cumulative  biogas generation  of 39.00 cm3 with a pH range of 4.6 – 6.6. It was found that, agricultural wastes such as groundnut shell, rice straw maize cobs and sugarcane bagasse which naturally have been dumped carelessly as domestic waste especially when co-digested can provide an alternative substrate for efficient biogas production.